1986
DOI: 10.1021/bi00355a039
|View full text |Cite
|
Sign up to set email alerts
|

Cycloheximide sensitivity in regulation of acyl coenzyme A:cholesterol acyltransferase activity in Chinese hamster ovary cells. 2. Effect of sterol endogenously synthesized

Abstract: We reported in another paper [Chang, C. C. Y., Doolittle, G. M., & Chang, T. Y. (1986) Biochemistry (preceding paper in this issue)] that in Chinese hamster ovary (CHO) cells activation of acyl coenzyme A:cholesterol acyltransferase (ACAT) activity by treating cells with cycloheximide was abolished by providing exogenous sterol in the medium. We now report that providing 20 mM DL-mevalonate to cells grown in sterol-free medium increases the ACAT activity by approximately 6-fold and diminishes the cycloheximide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…There was no difference found between reconstituted ACAT activities in the cell extracts obtained from each cell line grown with or without LDL (Table I). This is consistent with previous work from this laboratory (10,15,16,23) that suggested that changes in the ACAT protein content are not responsible for the regulation of enzyme activity by LDL. The reconstituted ACAT activities in CT60 and 25-RA cell extracts were found to be similar but the reconstituted ACAT activities in CT52 cell extracts were always '~50% greater than values obtained with 25-RA cell extracts.…”
Section: Cholesteryl Ester Synthesis and Cell Hybridization Analysissupporting
confidence: 93%
“…There was no difference found between reconstituted ACAT activities in the cell extracts obtained from each cell line grown with or without LDL (Table I). This is consistent with previous work from this laboratory (10,15,16,23) that suggested that changes in the ACAT protein content are not responsible for the regulation of enzyme activity by LDL. The reconstituted ACAT activities in CT60 and 25-RA cell extracts were found to be similar but the reconstituted ACAT activities in CT52 cell extracts were always '~50% greater than values obtained with 25-RA cell extracts.…”
Section: Cholesteryl Ester Synthesis and Cell Hybridization Analysissupporting
confidence: 93%
“…The mechanism of cholesterol ester accumulation in acinar cells of alcoholic or malnourished rats is unknown. Wilson et al suggested that longterm ethanol feeding would cause pancreatic cholesterol ester accumulation by affecting exchange of cholesterol between serum and pancreatic tissue,38 and it is well known that cholesterol uptake by the cell stimulates acyl-CoA cholesterol-acyltransferase (ACAT) activity producing cholesterol ester.39 40 This proposed mechanism is in agreement with our data, because serum cholesterol concentrations of rats with pancreatic steatosis (groups C, D, and E) were higher than those in rats with normal pancreatic morphology (groups A and B) (Table IV). (Table III, Table IV) and steatosis in alcoholic rats is also present without hypercholesterolaemia as has been reported by Tsukamoto et al 30 One such factor could be the metabolism of ethanol inside acinar cells inducing cholesterol ester formation.…”
Section: Discussionmentioning
confidence: 99%
“…ACAT activity assay in intact cells was performed as previously described (Chang and Chang, 1986). The incubation time with [ 3 H]-oleate-BSA was 2 h.…”
Section: Methodsmentioning
confidence: 99%